Factors related to the degree of hypertension in the working area of the Limboto Health Center - Nurain Afriani Walangadi; Zainuddin; Nur Ayun R. Yusuf (Universitas Muhammadiyah Palu, 2026)
Hypertension is a condition of increased blood pressure that is chronic and can cause serious complications if not controlled properly. Lifestyle factors such as physical activity, stress levels, and smoking behavior are thought to be related to the severity of hypertension. This study aims to analyze factors related to the degree of hypertension in the working area of the Limboto Health Center. This research method is quantitative with a correlational analytical design through a cross sectional approach. The population is all hypertensive patients totaling 4,575 people, and a sample of 98 respondents using purposive sampling techniques. The research instruments are the Global Physical Activity Questionnaire (GPAQ), Perceived Stress Scale (PSS), Global Adult Tobacco Survey (GATS). The data was analyzed using the Spearman Rank test. The results showed that most of the respondents had low physical activity (44.9%), moderate stress levels (42.9%), and moderate smoking behavior (36.7%). Based on the results of the Spearman Rank test, it was found that there was a significant relationship between physical activity and the degree of hypertension (p-value = 0.000 and the correlation coefficient r = -0.755), there was a significant relationship between the level of stress and the degree of hypertension (p-value = 0.000 and the correlation coefficient r = 0.469), and there was a significant relationship between smoking behavior and the degree of hypertension (p-value = 0.000 and the correlation coefficient r = 0.572). The conclusion of this study shows that there is a relationship between physical activity, stress levels, and smoking behavior with the degree of hypertension in people in the Limboto Health Center Working Area. The lower the physical activity, the higher the level of stress, and the more severe the smoking behavior, the higher the degree of hypertension in the respondents. Thus, the target of this research is expected to be the basis for health workers in the work area of the Limboto Health Center to increase promotive and preventive efforts through health education, routine screening, and improvement of healthy living behaviors to reduce the risk and severity of hypertension in the community.